2008
DOI: 10.1529/biophysj.108.142182
|View full text |Cite
|
Sign up to set email alerts
|

Protein Adsorption onto Organically Modified Silica Glass Leads to a Different Structure than Sol-Gel Encapsulation

Abstract: The secondary structures of two proteins were examined by circular dichroism spectroscopy after adsorption onto a series of organically modified silica glasses. The glasses were prepared by the sol-gel technique and were varied in hydrophobicity by incorporation of 5% methyl, propyl, trifluoropropyl, or n-hexyl silane. Both cytochrome c and apomyoglobin were found to lose secondary structure after adsorption onto the modified glasses. In the case of apomyoglobin, the alpha-helical content of the adsorbed prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Differences in gained volume of aerogels influenced their thickness. Aerogels obtained using TMS and MTMS were characterized by lower thickness, around 0.1 g/cm 3 and higher porosity, around 95%; however, aerogels prepared with the use of TMBS contained a thickness of 0.23 g/cm 3 and porosity of about 88%. It was also determined that silica aerogels prepared with use of organosiles containing metalohalogenic were turbid (clearness < 8%), and aerogels prepared with alkylalcoxysilanes were clear (80%).…”
Section: Obtaining Hydrophobic Silica Aerogelmentioning
confidence: 97%
See 1 more Smart Citation
“…Differences in gained volume of aerogels influenced their thickness. Aerogels obtained using TMS and MTMS were characterized by lower thickness, around 0.1 g/cm 3 and higher porosity, around 95%; however, aerogels prepared with the use of TMBS contained a thickness of 0.23 g/cm 3 and porosity of about 88%. It was also determined that silica aerogels prepared with use of organosiles containing metalohalogenic were turbid (clearness < 8%), and aerogels prepared with alkylalcoxysilanes were clear (80%).…”
Section: Obtaining Hydrophobic Silica Aerogelmentioning
confidence: 97%
“…For many years, a search for new methods of chemical surface modifications has been conducted for different forms of silica (2)(3)(4)(5). The presence of hydroxyl on the surface of silica materials greatly facilitates their modification, which allows for their wide application in analytical chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The first industrially used immobilized enzyme was prepared by adsorption of amino acid acylase on DEAE-cellulose [16]. Menaa et al (2008a) [17] reported the role of hydrophobic surfaces of nanoporous silica glasses on protein folding enhancement.…”
Section: Adsorptionmentioning
confidence: 99%
“…Instead, the formation of FeN Mod , which occurs at a higher protein to NP ratio, is responsible for the loss of helical content. It can also be argued that the formation of FeN Mod at high NP concentration is the result of less number of Cytc bound per NP molecule as discussed previously . Alternatively, at low NP concentration, the number of protein molecules adsorbed on the NP surface would increase.…”
Section: Discussionmentioning
confidence: 99%